Can the Lateral Habenula Crack the Serotonin Code? - Tchenio, Anna; Valentinova, Kristina; Mameli, Manuel (Frontiers in Synaptic Neuroscience, 2016)
The lateral habenula (LHb) and the serotoninergic system both contribute to motivational states by encoding rewarding and aversive signals. Converging evidence suggests that perturbation of these systems is critical for the pathophysiology of mood disorders. Anatomical and functional studies indicate that the serotoninergic system and the LHb are interconnected in a forward-feedback loop. However, how serotonin release modifies the synaptic and cellular properties of LHb neurons and whether this has any behavioral repercussions remain poorly investigated. In this review article, we discuss insights gained from rodents and humans regarding the implications of the serotonin system and the LHb in aversion encoding and related disorders. We then describe the type, properties and pharmacology of serotoninergic receptors expressed throughout the LHb. Finally, we discuss physiological data reporting how serotoninergic signaling modifies synaptic transmission and neuronal activity within the LHb. Altogether, we combine a mechanistic- and circuit-level knowledge to provide an overview on how the LHb integrates serotoninergic signals, a process potentially contributing to LHb-dependent encoding of valenced external stimuli.